2012
DOI: 10.5603/fhc.2012.0080
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene induces cell cycle arrest and apoptosis in MOLT4 human leukemia cells

Abstract: Pterostilbene, a polyphenolic compound present in grapes and other fruits, has been demonstrated to inhibit growth and induce apoptosis and autophagy in some cancer cell types. We found that pterostilbene at the IC 90 concentration of 44 µM inhibited proliferation and induced apoptosis in MOLT4 human leukemia cells. Treatment with pterostilbene resulted in a transient accumulation of cells in the G 0 /G 1 -cell cycle phase followed by the S-phase arrest. Pterostilbene-induced apoptotic death of MOLT4 cells was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 19 publications
3
3
0
1
Order By: Relevance
“…In our study, we showed that pterostilbene has dose-dependent cytotoxic effects on Jurkat and Hut-78 cells after 24 and 48 h treatment. This effect has also been observed in acute myeloid leukemia and the MOLT-4 human lymphoblastic leukemia cell line [21, 22]. At the same time, we found that the doses of pterostilbene we used in our present study are safe.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, we showed that pterostilbene has dose-dependent cytotoxic effects on Jurkat and Hut-78 cells after 24 and 48 h treatment. This effect has also been observed in acute myeloid leukemia and the MOLT-4 human lymphoblastic leukemia cell line [21, 22]. At the same time, we found that the doses of pterostilbene we used in our present study are safe.…”
Section: Discussionsupporting
confidence: 86%
“…It has been shown that dose-dependent PTER induces apoptosis in HL60 cell at concentrations similar to those used in our investigation [32,33,42,43]. Furthermore, our research confirmed that, PTER induces apoptosis in MOLT 4 [43], MV4-11, U937, and THP-1 human leukemia cell lines [32].…”
Section: Discussionsupporting
confidence: 87%
“…Antitumor activity of stilbene derivatives has been shown in vitro in many cell lines. The induction of apoptosis in cancer cells by stilbene derivatives is well-documented [17,26,32,33,34,35,36,37,38,39,40,41,42,43]. Stilbene derivatives have been shown to have antitumor activity due to several mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 Also, PTS has been shown to cause a transient accumulation of cells in the G 0 /G 1 -cell cycle phase followed by the S-phase arrest in MOLT4 human leukemia cells. 50 Almost the same observations were reported by 10 PTS-induced apoptosis due to ROS generation in MCF7 and nitric oxide over production in PC3 cells. It was concluded previously that PTS exerted its anticancer action in breast cancer by arresting cells in G0/G1, G2/M or S phase.…”
Section: Cell Cycle Progression Analysissupporting
confidence: 65%